(untitled) (Czech Journal of Multidisciplinary Innovations, 2024)
This article is about the lexical units representing meteorological concepts in the language. Meteorology is a branch of the atmospheric sciences (which include atmospheric chemistry and physics) with a major focus on weather forecasting. The term meteorological is an adjective that relates to meteorology, that is to say to the study of phenomena atmospheric and climatic conditions. It is used to describe anything related to the science of weather or events occurring in the atmosphere terrestrial.